Analysis of Criminal Liability for Perpetrators of Persecution Based on Criminal Theory (Study of Decision Number 96/Pid.B/2018/PN.Kwg) - Lesmana, Rikal; Maman, Ade; Setiady, Tri (PT. Anagata Sembagi Education, 2025)
This study examines criminal liability and judicial considerations in cases of persecution in Indonesia, focusing on Decision Number 96/Pid.B/2018/PN.Kwg. Using a normative juridical approach, it analyzes relevant legal provisions, particularly Articles 49 and 351 of the Indonesian Criminal Code. The case involves Nurhidayat, who assaulted the victim, Fahrul, during a dispute over motorcycle credit repayment. The research investigates the form of criminal responsibility for the crime of persecution and the judge's reasoning in sentencing the defendant. The findings show that the Karawang District Court's decision did not fully align with justice and legal certainty principles. Nurhidayat was sentenced to three years in prison, despite mitigating factors such as his remorse, cooperative attitude, and role as the family’s breadwinner. The study concludes that the court’s decision did not adequately consider the juridical and non-juridical aspects, resulting in a sense of injustice for both the victim and the defendant. This research recommends that judges, when determining sanctions, should consider the proportionality of the crime and account for all aspects of justice. This would ensure that decisions better reflect fairness and provide clearer legal certainty, aligning with the principles of justice, legal certainty, and the protection of citizens' rights in the criminal justice system.